Prolonged Duration of Blood Pressure Drops During General Anesthesia Is Associated With Worse Outcomes After Mechanical Thrombectomy - Xu, Chao; Lin, Gaoping; Zhang, Zheyu; Jin, Tianyu; Li, Ning; Mao, Hui; Ye, Sasa; Yang, Zongming; Geng, Yu; Shi, Zongjie (Frontiers in Neurology, 2021)
Background and Purpose: Optimal peri-procedural management of blood pressure during mechanical thrombectomy (MT) remains controversial. This study aimed to investigate the relationship between duration of blood pressure drop during general anesthesia and outcome in large vessel occlusion (LVO) patients treated with MT. Methods: We retrospectively reviewed our prospectively collected data for LVO patients treated with MT between January 2018 and July 2020. Intraprocedural mean arterial pressure (MAP) was recorded every 5 minutes throughout the procedure. Baseline MAP minus each MAP value recorded during general anesthesia was defined ΔMAP. Cumulated time (in minutes) and longest continuous episode (in minutes) with ΔMAP more than 10, 15, 20, 25 and 30 mmHg were calculated, respectively. Poor outcome was defined as 90-day modified Rankin score (mRS) 3–6. Associations between cumulated time of different ΔMAP thresholds and poor outcome were determined using binary logistic regression models. Results: A total of 131 patients were finally included in the study. After controlling for age, atrial fibrillation, baseline NIHSS, baseline ASPECTS, procedure duration of MT and times of retrieval attempts, the results indicated that cumulated time of MAP drop more than 10 mm Hg (OR 1.013; 95% CI 1.004 to 1.023; P=0.007) and 15 mm Hg (OR 1.011; 95% CI 1.002 to 1.020; P=0.017) were independently associated with poor outcome Conclusion: Prolonged episodes of intraprocedural MAP lowering were more likely to have poor outcome in LVO patients following MT with general anesthesia, which might be helpful in guiding intraprocedural hemodynamic management of patients under general anesthesia.